A health promotion model approach in exploring self-management and glycemic control in type 2 diabetes: the moderating effects of self-efficacy and social support - Sylvi Ndatila Amunkete; Elihuruma Eliufoo Stephano; Mtoro J. Mtoro; Feng Hui (Frontiers in Clinical Diabetes and Healthcare)
BackgroundAs the prevalence of diabetes and its related complications continues to rise, understanding the factors that influence glycemic control is crucial for improving patient outcomes. This study aimed to explore the roles of self-management, social support, and self-efficacy in moderating fasting blood glucose (FBG) levels in individuals with type 2 diabetes mellitus (T2DM).MethodsA health facility-based cross-sectional study was conducted in Windhoek, Namibia with a sample size of 315 T2DM patients receiving follow-up care. Descriptive statistics and Pearson correlation analysis were conducted to examine the relationship between self-management and FBG. Linear regression and moderation analyses were used to determine the moderating effects.ResultsThe study revealed 34.3% engaged in self-monitoring of FBG, while medication adherence was high at an average of 7 days. A significant negative correlation between self-management practices and FBG levels was identified (r = -0.349, p < 0.028). Self-management, self-efficacy, and social support accounted for 43.1% of FBG variation, with self-management emerging as a significant predictor (β = -0.903, p < 0.001). Additionally, social support and self-efficacy significantly moderated the relationship between self-management and FBG levels.ConclusionThis study showed the significant moderating roles of social support and self-efficacy in the relationship between self-management practices and FBG levels in patients with diabetes. These results highlight the importance of comprehensive diabetes management programs focusing on individual behavioral changes, enhancing social support networks, and boosting self-efficacy.